A simple and rapid method for detecting the pesticide fipronil on egg shells and in liquid eggs by Raman microscopy. (February 2019) - Tu, Qin; Hickey, Michael E.; Yang, Tianxi; Gao, Siyue; Zhang, Qingmiao; Qu, Yanqi; Du, Xinyi; Wang, Jinyi; He, Lili
Abstract: The pesticide fipronil was recently involved in a "poisonous eggs" scandal which resulted in substantial economic losses and public health risks. We report a simple and rapid method which can be implemented to detect fipronil on egg shells and in liquid eggs by Raman spectrometry. Fipronil rapidly crystallizes when solubilized in water-acetone solution (1:6, V/V, acetone/water). This process can be visually observed by naked eyes, suggesting a possible rapid and instrument-free screening action. Then, fipronil crystals were concentrated and recovered on a gold-coated glass slide for further identification and quantification by Raman microscopic analyses. A standard curve was established to quantify fipronil within the range of 1–500 mg/L ( r 2  ≥ 0.997), based on the unique fipronil Raman shift at 2256 cm −1 . Acetone based extraction recovered fipronil at three spiked levels of 5, 60 and 100 mg/kg on chicken egg shells and in liquid eggs from 59.91% to 81.72% and 85.97% to 152.46%, respectively. The limit of detection translated to the weight of liquid egg (0.32 mg/kg) and the surface area of an egg shell (0.065 mg/m 2 ). In conclusion, this method has demonstrated a strong capacity for the rapid ( < 30 min) detection of fipronil on chicken egg shells and in liquid eggs. Highlights: A simple and rapid Raman microscopic method was developed to detect fipronil. The first time of using Raman microscopy to detect the fipronil on egg shell and in liquid egg. The method was based on the difference of fipronil solubility in acetone and water. The limit of detection was 0.32 mg/kg in liquid eggs and 0.065 mg/m 2 on egg shells.